Single-step fabrication of high-density microdroplet arrays of low-surface-tension liquids - Feng, Wenqian; Li, Linxian; Du, Xin; Welle, Alexander; Levkin, Pavel (Advanced materials, 2016)
A facile approach for surface patterning that enables single-step fabrication of high-density arrays of low-surface-tension organic-liquid microdroplets is described. This approach enables miniaturized and parallel high-throughput screenings in organic solvents, formation of homogeneous arrays of hydrophobic nanoparticles, polymer micropads of specific shapes, and polymer microlens arrays.
Gesehen am 15.05.2020